2015
DOI: 10.1186/s12906-016-1004-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new plant extract for androgenic alopecia treatment using a non-radioactive human hair dermal papilla cell-based assay

Abstract: BackgroundAndrogenic alopecia (AGA) is a major type of human scalp hair loss, which is caused by two androgens: testosterone (T) and 5α-dihydrotestosterone (5α-DHT). Both androgens bind to the androgen receptor (AR) and induce androgen-sensitive genes within the human hair dermal papilla cells (HHDPCs), but 5α-DHT exhibits much higher binding affinity and potency than T does in inducing the involved androgen-sensitive genes. Changes in the induction of androgen-sensitive genes during AGA are caused by the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Many beauty products are currently available that incorporate C. asiatica extracts, such as cosmetic creams, hand and body lotions, eye gel, and face mask products (Bylka et al, 2014). A previous study found that C. asiatica extract enlarged hair follicles (Jain and Dass, 2015) and inhibited the activity of 5α-reductase that causes hair loss (Jain et al, 2016). However, few hair care or restoration products contain the extract, as its effect on the hair root remains unclear; the molecular mechanisms involved in plant extracts modulating gene expression are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Many beauty products are currently available that incorporate C. asiatica extracts, such as cosmetic creams, hand and body lotions, eye gel, and face mask products (Bylka et al, 2014). A previous study found that C. asiatica extract enlarged hair follicles (Jain and Dass, 2015) and inhibited the activity of 5α-reductase that causes hair loss (Jain et al, 2016). However, few hair care or restoration products contain the extract, as its effect on the hair root remains unclear; the molecular mechanisms involved in plant extracts modulating gene expression are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was based on the use of a newly developed nonradioactive human hair dermal papilla cell-based assay, which directly detects dihydrotestosterone (DHT, 2), the enzymatic product, by high performance thin layer chromatography (HPTLC). 20,21) Even though the steroid 5α-reductase inhibitory activity of 5a was not as potent as dutasteride (4), the discovery of a new chemical scaffold has provided a potential for the development of a new group of steroid 5α-reductase inhibitors. Thus, we hypothesized that compounds having a furanonaphthoquinone, similar to 5a and a more simplified structure, naphthoquinone, would be used as the potential steroid 5α-reductase inhibitors.…”
mentioning
confidence: 99%
“…The steroid 5α-reductase inhibition was measured based on the amount of dihydrotestosterone (2) produced, determined using HPTLC as previously described. 20,21) Molecular docking using the homologous protein template of steroid 5α-reductase type 1 19) was performed via AutoDock Vina 25) to predict the biomolecular interaction between the 5α-reductase-reduced nicotinamide adenine dinucleotide phosphate (NADPH) binary complex and the respective furanonaphthoquinones. Herein, an essential pharmacophore and inhibitory activity of a potential steroid 5α-reductase inhibitor are discussed.…”
mentioning
confidence: 99%
“…Various methods are used to maintain the fertility and health of hair and minimalize and prevent hair problems. Health care for the hair can be done by way of cleaning your hair regularly and wear hair growth [1][2][3].…”
Section: Introductionmentioning
confidence: 99%